PENINGKATAN KUALITAS PERKULIAHAN GEOGRAFI POLITIK DENGAN MODEL PEMBELAJARAN INTERPERSONAL COMMUNICATION (IC) DI UNIVERSITAS PGRI PALEMBANG - Boby Agus Yusmiono (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
The problem is "How to Improve the Quality of Political Geography Lectures with Interpersonal Communication Learning Model (IC) at PGRI University of Palembang?".This research used are qualitative data, in the form of primary data and secondary data. Primary data obtained directly from the observation. Secondary data obtained from the documentation of the test results and the final value of fifth semester in subjects Political Geography. As a lecturer of Political geography lecture for the fifth semester of the teaching scholar. This study uses an action research model of Kemmis and Taggart, which is spiral-shaped from one cycle to the next. According Kemmis and Taggart there are several stages namely: Planning (Plan), Action (act), Observation (Observe) and Reflection (reflect). The result of the observation from 34 students who studied Political Geography during the first cycle of score only 51% who dared to communicate, but in the second cycle showed an increase of 82% level of courage to communicate students. While based on the test the first cycle value of the test student value of 67 and in the second cycle has increased that is equal to 85. Based on data observation sheet, and the tests concluded that the learning model of Interpersonal Communication (IC) creativity and communicative activities of students semseter 5A in the course of Political Geography has increased. It is also seen from the Semester Results List of Participants and the Final Score (DPNA) Politics Geography course students, the average student good value that is equal to 83%.